In defence of departure: Justice and the right to leave. Issue 1 (3rd March 2017) - Blake, Michael
Abstract : I have previously argued that liberal states are limited in the means by which they can respond to the emigration of skilled professionals. In particular, the right to leave is a right of sufficient strength that it must be defended even when its suspension would create more robust institutions for those in the state of origin. Against this, four critics offer arguments in favour of positions which – like those of Gillian Brock – would allow states more leeway in their legitimate policy options. These critics offer arguments from legitimate authority; from solidarity; from burden-sharing under non-ideal circumstances; and from gradualism in both the acquisition and dissolution of membership. In this paper, I defend my original view against these objections. I am grateful to these critics, as well as the other authors who have written in this volume.